PENGARUH STRUKTUR KEPEMILIKAN DAN KEBIJAKAN KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Kaluti, Stephani Novitasari Christianingsih; Purwanto, Agus (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the effect of ownership structure and financial policy on firm value. Firm value measured by the Price to Book Value, using data companies listed on Stock Exchanges in Indonesia. The population in this study is companies listed on Stock Exchanges in Indonesia. Samples were selected using purposive sampling method. The analysis used is multiple regression analysis. Before being tested with multiple regression first tested the classical assumptions. Results showed that together the independent variables of institutional ownership, managerial ownership, debt policy, dividend policy, and investment policy affects the dependent variable firm value. Whereas individually, variable dividend policy and institutional ownership and a significant positive effect on firm value. Investment policy significant negative effect on firm value. While managerial ownership variables and debt policy does not significantly affect the firm value.